Factors Related to Work Accidents for Workers in the Production Division of Palm Oil Mills, Bangkinang District, Kampar Regency in 2021 - Rahayu Aishakina; Mitra Mitra; Herniwanti Herniwanti; Oktavia Dewi; Endang Purnawati Rahayu (Budapest International Research and Critics University, 2021)
This study aims to determine factors related to work accidents for workers in the production division of Palm Oil Mills, Bangkinang District, Kampar Regency in 2021. The type of research used is quantitative with a cross sectional study design. The sample in this study was 86 people. Data analysis was done by bivariate and multivariate. The results of the study of variables related to work accidents from the bivariate analysis were age (p-value=0.004), years of service (p-value=0.007), knowledge (p-value=0.004), attitude (p-value=0.007), occupational safety and health (K3) training (p-value=0.004), and use of personal protective equipment (APD) (p-value=0.000). The most dominant variable on work accidents is the use of APD (p-value=0.032).